COMPARISON AND FUNCTIONAL ANALYSIS OF SINGLE-BUNDLE ANTERIOR CRUCIATE LIGAMENT RECONSTRUCTION ALONE WITH LATERAL EXTRA-ARTICULAR TENODESIS AS AN ADJUNCT TO ANTERIOR CRUCIATE LIGAMENTRE CONSTRUCTION IN ANTEROLATERAL INSTABILITY - RAJA RAMESH BADAVATH; LALITH MOHAN C; CHANDRA SHEKHAR P; JOSHI VINAY KUMAR EJ (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The aim of this study is to compare the functional outcome of ACLR alone, with patients who underwent ACLR with LET.ACL injuries rarely occur in isolation, and associated meniscal, chondral, and ligamentous lesions all influence the outcome of treatment Materials and methods: This prospective study conducted in 30 patients with ACL deficient knee with high grade pivot (grade-II &grade-III) Skeletally mature to 56 years of age , 2 or more of: competitive pivoting sport, Chronic ACL insufficiency, Revision ACLR and Generalized ligament laxity - Beighton score of 4 greater. Results: A total of 30 patients were evaluated in this study.15 cases were operated for ACLR and 15 cases for ACLR + LET. Most of the patients were in the age group of 21-30 with all male gender indicating ACL injuries are common in young males with history of road traffic accident (63.33%) at the time of injury. The mean operating time in our study (also the total tourniquet time) was 110 minutes (range 100 - 130 minutes). Instability was controlled well in ACLR + LET group .Two patients in ACLR+LET group have complained of instability episodes. Preoperatively, Grade 2 pivot shift was observed in 80% in control and 33.33% in other group. Grade 3 pivot shift on examination was found in 20% in control group and 66.66% in experimental group. Post-surgery patients who received ACLR alone had Grade 1 pivot in 60% , Grade 2 in 33.33% and Grade 3 in 6.67%. Combined group (ACLR+LET) had grade 1 in 33.33, Grade 2 in 60% and Grade 3 pivot in 66.66%. Regarding preoperative IKDC scores, patients treated with ACLR alone had 26.66% below 45, 40% between 45-55, 6.66% in 60-70,70-80 and in patients treated with both ACLR+LET had 6.66% in 40-50, 20% in 50-60,46.66% in 60-70, 26.66% in 70-80 before surgery. Post-surgery, patients in both groups had excellent scores (90-100 IKDC score). Conclusions: The combination of LET and intra-articular ACLR is effective in eliminating the high-grade pivot-shift phenomenon. Adding a lateral extra-articular tenodesis can improve patient outcome without the need for future revision ACL surgery and its obligatory intense postoperative rehabilitation, in moderately active patients.